Calibration of the mixing-length theory for structures of helium-dominated atmosphere white dwarfs - Cukanovaite, Elena; Ludwig, Hans-Günter (Monthly notices of the Royal Astronomical Society, 2019)
ABSTRACT. We perform a calibration of the mixing-length parameter at the bottom boundary of the convection zone for helium-dominated atmospheres of white dwarf